Interaction between chicken intestinal microbiota and protein digestion - Apajalahti, J.; Vienola, K. (Animal feed science and technology, 2016)
•Small intestinal bacteria havesimilar aminoacid requirements as the host.•Lactic acid bacteria and the host compete for dietary amino acids.•Protein escaping ileum is subject to putrefaction in the caecum.•Putrefaction produces toxin metabolites such as amines, indoles and ammonia.•Feed enzymes potentially alleviate problems of microbial protein metabolism. The different sections of the broiler chicken intestinal tract are inhabited by specialist microbiota adapted to the physicochemical conditions, host physiology and available nutrients of the specific habitat. The small intestine is dominated by lactic acid bacteria which have complex nutrient requirements resembling those of the chicken host itself. Lactobacilli are unable to synthesise amino acids for their anabolism and are therefore highly dependent on amino acid availability in the growth environment. Thus, in the small intestine there is competition for amino acids between the microbiota and the chicken host. According to rough estimates, lactobacilli in the small intestine may assimilate 3–6% of total dietary amino acids. If the protein is highly digestible and amino acids are largely absorbed in the upper small intestine, where bacterial growth is suppressed, the proportion captured by the host may be higher. Exogenous enzymes which promote protein digestion are also likely to provide a competitive advantage to the chicken, offering less growth potential for amino acid-dependent bacteria. Protein escaping the ileum comprises resistant protein of dietary origin, protein assimilated to intestinal bacteria and endogenous protein synthesised and secreted by the host, the latter synthesised in host tissues from dietary amino acids and thus representing true endogenous protein. Activities of small intestinal bacteria affect the size of the microbial protein fraction and also the production of endogenous proteins originating from mucin, epithelial cells and antibodies. Ileal bypass protein is subject to fermentation by putrefactive bacteria in the caecum. Putrefaction produces many harmful and toxic compounds, which in high concentrations may have adverse effects on chicken growth and performance. The protein fermentation products include amines, indoles, phenols, cresol and ammonia, which can all negatively affect host or cell health. All actions to reduce the amount of ileal bypass protein potentially also reduce production of toxic protein fermentation metabolites in the caecum. Enzymes which facilitate protein digestion in the upper intestine and soluble carbohydrates resistant to ileal digestion both reduce caecal putrefaction. In the distal intestine, saccharolytic fermentation is preferred and putrefaction accelerates only when utilisable carbohydrates are depleted. Soluble oligo- and polysaccharides are produced in situ by non-starch polysaccharide degrading enzymes and can also be added directly to the diet as health-promoting prebiotics.